Komunikasi Simbiolik Dalam Masyarakat - Effendy, Erwan; Fatika, Annisa; Harahap, Zakiah Mahrani; Deansyah, Reti Miranda (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
The purpose of this study is to find out about symbionic communication in social life, in which this study uses qualitative methods in the form of literature review methods from previous researchers, as well as other reference sources such as articles and opinions of experts used by researchers. Communication is a symbolic process that is a basic human need, symbolic or the use of symbols, and that is what distinguishes humans as creatures from other creatures. According to Ernst Cassier said that the superiority of humans over other creatures is their specialty as animal symboliccum. Communication is also a delivery of thoughts or feelings by one person to another by using symbols that are meaningful to both parties, in certain situations communication uses certain media to change the attitude or behavior of a person or a number of people so that there is a certain effect that is expected. Keywords: Symbolic Communication, Society, and Interaction